The Use of Multimodal and Interactive Digital Teaching Materials in 21st Century Mathematics Learning (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Multimodal interactive digital teaching materials are learning materials that contain learning materials that are in accordance with learning objectives designed by utilizing various resources including text, images, audio, video, music, and social media in the form of YouTube, tik tok, and appropriate internet links and are interactive because they are digital based. The aim of this activity is to improve teachers' understanding and skills in using multimodal digital teaching materials in 21st century learning. Participants in the community service activity were 25 participants consisting of teachers. This activity was carried out at MTs Al Gebra, Sorong City and MI Al Islah, Sorong City. The methods used in multimodal digital training are material presentation, discussion and training simulation. The results of this training have a positive impact on teachers in managing the learning process. This can be seen from the analysis results that 80% of participants have increased knowledge, 80% of participants have increased creativity and 80% of participants need continuous training in increasing knowledge to prepare themselves in facing the digital era 4.0.